2013 IEEE International Conference on Communications (ICC) 2013
DOI: 10.1109/icc.2013.6655189
|View full text |Cite
|
Sign up to set email alerts
|

Design for change: Information-centric architecture to support agile disaster response

Abstract: This paper presents a case for the adoption of an information-centric architecture for a global disaster management system. Drawing from a case study of the 2010/2011 Queensland floods, we describe the challenges in providing every participant with relevant and actionable information. We use various examples to argue for a more flexible information dissemination framework which is designed from the ground up to minimise the effort needed to fix the unexpected and unavoidable information acquisition, quality, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The classification of buildings is done in four classes in Table (6), taking into account the simultaneous impact of ten building Characteristics of Table (7). E10 2= [15][16][17][18][19][20] E10 3= [12][13][14][15] E10 4= [1][2][3][4][5][6][7][8][9][10][11][12] We display the set of buildings as set X as follows:…”
Section: Case Studymentioning
confidence: 99%
“…The classification of buildings is done in four classes in Table (6), taking into account the simultaneous impact of ten building Characteristics of Table (7). E10 2= [15][16][17][18][19][20] E10 3= [12][13][14][15] E10 4= [1][2][3][4][5][6][7][8][9][10][11][12] We display the set of buildings as set X as follows:…”
Section: Case Studymentioning
confidence: 99%
“…The limitation of IP-based networks compared with NDN in disaster response has been discussed in several studies [2][3][4]. There are three main advantages of NDN over IP architecture.…”
Section: Named Data Networking Advantages Over Ip-based Network In Di...mentioning
confidence: 99%
“…Because of these challenges, it is necessary to find a network solution that has mobility built-in support and enable location-independent, role-based group communication between responders. In recent years, several studies [2][3][4] have shown that Information-Centric Networking (including NDN-one of its architectures) can improve IP-based network weaknesses in providing these mentioned features in disaster. Specifically, NDN uses the content name as the main entity inside the network to route the packet instead of IP address-content location in IP-based network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation